Internet memes related to the COVID-19 pandemic as a potential coping mechanism for anxiety - Akram, U; Irvine, K; Allen, SF; Stevenson, JC; Ellis, JG; Drabble, J (Springer Nature, 2021)
This study examined whether significantly anxious individuals differed from non-anxious individuals in their perceptual ratings of internet memes related to the Covid-19 pandemic, whilst considering the mediating role of emotion regulation. Eighty individuals presenting clinically significant anxiety symptoms (indicating ≥ 15 on the GAD-7) and 80 non-anxious controls (indicating ≤ 4) rated the emotional valance, humour, relatability, shareability, and offensiveness of 45 Covid-19 internet memes. A measure of emotion regulation difficulties was also completed. The perception of humour, relatability, and shareability were all greater amongst anxious individuals relative to non-anxious controls. These differences were not mediated by emotion regulation deficits. Internet memes related to the current Covid-19 pandemic may tentatively serve as coping mechanism for individuals experiencing severe symptoms of anxiety.